Liquidity, Firm Size, and Productivity as Determinants of Sukuk Ratings in Indonesian Listed Firms - Aiyubi Rahman; Kartini Kartini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The purpose of this study is to analyze the influence of liquidity, company size, and productivity on sukuk ratings at PT Pemeringkat Efek Indonesia. This study employs a quantitative approach using secondary data obtained from the financial statements of companies issuing sukuk during the 2020–2023 period. The research sample consists of 12 companies listed on PT Pefindo, with a total of 48 observations. Data were analyzed using the Panel Data Regression with the Fixed Effect Model and selected through a purposive sampling technique. The analysis results indicate that liquidity does not significantly influence sukuk ratings, suggesting that a company’s current asset level, although important, is not a primary focus in assessing sukuk ratings. Conversely, company size has a significant positive effect, indicating that larger companies tend to receive better sukuk ratings. Productivity, on the other hand, also has no significant effect, implying that asset efficiency is not always a main consideration in sukuk rating evaluation. The novelty of this study lies in integrating liquidity, firm size, and productivity within the framework of signaling theory to explain their joint influence on sukuk ratings. The results of this study can be used by sukuk-issuing companies to focus more on managing firm size as a key factor in enhancing sukuk attractiveness in the Islamic capital market. Furthermore, this research enriches the Islamic finance literature by identifying factors affecting sukuk creditworthiness and provides useful insights for investors in evaluating the risks and potential returns of sukuk investments.